Work–family spillover and crossover effects of authentic leadership in China. (26th September 2018) - Zhou, Aiqin; Yang, Ziwei; Kwan, Ho Kwong; Chiu, Randy K
Abstract : This study investigated the relationship between authentic leadership as perceived by employees and romantic love as rated by their spouses. It also focused on the mediating role of employee work‐to‐family positive spillover and the moderating role of employee work–home segmentation preference. Data from 200 employee–spouse couples collected in three waves in China indicated that work‐to‐family positive spillover mediated the relationship between authentic leadership and romantic love. In addition, work–home segmentation preference attenuated the relationships among authentic leadership, work‐to‐family positive spillover, and romantic love, as well as the indirect effect of work‐to‐family positive spillover on the relationship between authentic leadership and romantic love. Our findings make important theoretical contributions and contribute practical insight into the leadership and work–family literature. Key points: The findings reveal that authentic leadership is effective in inducing followers' work–family positive spillover. Employees' work–family positive spillover helps their spouses promote romantic love towards the employees. Work–home segmentation preference attenuates the relationships among authentic leadership, positive spillover, and romantic love.